1994
DOI: 10.1128/aac.38.9.2175
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of Epstein-Barr virus thymidine kinase

Abstract: Purified recombinant protein encoded by the BXLF-I open reading frame of the Epstein-Barr virus genome has thymidine kinase activity. The substrate behaviors of various nucleosides toward this enzyme were tested. Halogenated deoxyuridines, zidovudine, and bromovinyldeoxyuridine are efficient substrates, while acyclovir and dihydroxypropylmethylguanine are relatively poor substrates for the Epstein-Barr virus thymidine kinase.Like most other herpesviruses, Epstein-Barr virus (EBV) encodes a virus-induced protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…D290E and T298S, which are in site 1, have been suggested to be involved in ATP binding and were tested as controls. Results were similar to those reported by Tung and Summers [27], Mg 2+ is the preferred ion for EBV TK, Mn 2+ is less favoured and Zn 2+ could inhibit its activity, as shown in Figure 3. Among the mutants tested, only D392E revealed an altered pattern of metal-ion usage, where nearly similar activities were found for all three metal ions.…”
Section: Metal-ion Usage Of the Site 3 Mutantssupporting
confidence: 80%
See 1 more Smart Citation
“…D290E and T298S, which are in site 1, have been suggested to be involved in ATP binding and were tested as controls. Results were similar to those reported by Tung and Summers [27], Mg 2+ is the preferred ion for EBV TK, Mn 2+ is less favoured and Zn 2+ could inhibit its activity, as shown in Figure 3. Among the mutants tested, only D392E revealed an altered pattern of metal-ion usage, where nearly similar activities were found for all three metal ions.…”
Section: Metal-ion Usage Of the Site 3 Mutantssupporting
confidence: 80%
“…A biochemical study revealed that EBV TK has K m values of 22 µM for thymidine and 25 µM for ATP [27]. Substrate specificity has also been determined by several groups [27,28]. However, the structurefunction relationship of EBV TK has been addressed rarely.…”
Section: Introductionmentioning
confidence: 99%
“…nucleoside analogs. [9][10][11] We thus compared tk from HSV1, varicella-zoster virus (VZV), equine herpes virus type-4 (EHV4) and Epstein-Barr virus (EBV) for their capacity to sensitize tumor cells to ACV, GCV and BVDU.…”
Section: Abstract: Nucleoside Analogs; Cancer; Fusion Proteinsmentioning
confidence: 99%
“…These highly active enzymes are required for efficient infection of primary epithelial cells (13) and reactivation of lytic replication from neuronal latency (7). In contrast, the gammaherpesvirus TKs are strict thymidine kinases that do not phosphorylate the other nucleosides and have greatly reduced enzymatic activity compared with the alphaherpesvirus TKs (16,20,21,30,46). It is not known whether these enzymes are required for lytic replication in terminally differentiated oral epithelial cells, following lytic reactivation from latently infected B lymphocytes or from endothelial tumor cells in the case of Kaposi's sarcoma-associated herpesvirus (KSHV).…”
mentioning
confidence: 99%